2020
DOI: 10.1038/s41598-020-58582-7
|View full text |Cite
|
Sign up to set email alerts
|

$${\mathscr{PT}}$$ -symmetry from Lindblad dynamics in a linearized optomechanical system

Abstract: The optomechanical state transfer protocol provides effective, lossy, quantum beam-splitter-like dynamics where the strength of the coupling between the electromagnetic and mechanical modes is controlled by the optical steady-state amplitude. By restricting to a subspace with no losses, we argue that the transition from mode-hybridization in the strong coupling regime to the dampeddynamics in the weak coupling regime, is a signature of the passive parity-time (PT ) symmetry breaking transition in the underlyin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 37 publications
(52 reference statements)
0
15
0
Order By: Relevance
“…Most models [35][36][37][38][39] start with a non-Hermitian Hamiltonian (containing complex frequencies) that is applicable only in the classical limit where the number of energy quanta is much larger than one. For dissipative open quantum systems, one can write down a Lindblad equation from which one can get a non-Hermitian Hamiltonian by ignoring quantum jumps [62,66,84,85,88,121,122]. This approach has been generalized to gain-loss systems, with and without neglecting the quantum jumps, by writing down Lindblad terms for gain and loss phenomenologically [44,86,87,116,123].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most models [35][36][37][38][39] start with a non-Hermitian Hamiltonian (containing complex frequencies) that is applicable only in the classical limit where the number of energy quanta is much larger than one. For dissipative open quantum systems, one can write down a Lindblad equation from which one can get a non-Hermitian Hamiltonian by ignoring quantum jumps [62,66,84,85,88,121,122]. This approach has been generalized to gain-loss systems, with and without neglecting the quantum jumps, by writing down Lindblad terms for gain and loss phenomenologically [44,86,87,116,123].…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics generated by a non-Hermitian Hamiltonian is not unitary, and such dynamics can result from an open quantum system coupled to one or more environments (baths). Non-Hermitian Hamiltonians arising out of phenomenological Lindblad equations have been theoretically explored in several recent works (for example, [84][85][86][87][88]). However, a complete microscopic theory of an open quantum system showing the emergence of a non-Hermitian Hamiltonian with a PT transition starting from a fully Hermitian Hamiltonian description of a system coupled to multiple baths has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…But majority of works phenomenologically assume a non-Hermitian Hamiltonian and quantum and thermal fluctuations are ignored. Only recently some works have gone beyond such descriptions, deriving non-Hermitian dynamics from more microscopic quantum theories (for example, [70,72,[81][82][83][84][85][86][87][88]). On the other hand, classifying all kinds of non-Hermitian Hamiltonians and their relations to topology has remained an extremely active direction of research (for example, [76,[89][90][91][92][93][94]).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to an NHH, the Liouvillian also accounts for the presence of quantum jumps. The extension of EPs of NHHs to those based on Liouvillians [57] has shown that quantum jumps can play a crucial role in the properties of EPs [44,[58][59][60][61][62][63]. Furthermore, the evolution of a density matrix of an open quantum system is described by a completelypositive and trace-preserving (CPTP) linear map.…”
Section: Introductionmentioning
confidence: 99%